PENGARUH LEVERAGE DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2010-2013) - Dian Mustika Sara; Azwir Nasir; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research is to find out the effect of leverage and corporate governance on tax avoidance. This research was conducted at the manufactur companies listed on the Stock Exchange in the observation period 2010-2013. Sampling method used was purposive sampling method with a sample of 11 companies during the observation period of 4 years in a row for a total of 44 samples. The results of this study indicate that the institutional ownership has significant value 0,000 and a positive effect on tax avoidance, while the intensity of the audit committe meetings has significant value 0,032 and a negative effect on tax avoidance. Leverage, percentage of independent commissioner and audit quality has no significant effect on tax avoidance. Based on total adjusted R-Square results proved that on the variable leverage, institutional ownership, percentage of independent commissioner, the intensity of the audit committe meetings and audit quality effect on tax avoidance results of 49.4% while the rest of 50,6% were affected by other variables that were not performed in this study.Keywords: leverage, institutional ownership, audit committe, audit quality and tax avoidance